Time-of-day dependent effects of midazolam administration on myocardial injury in non-cardiac surgery - Prin, Meghan; Pattee, Jack; Douin, David J.; Scott, Benjamin K.; Ginde, Adit A.; Eckle, Tobias (Frontiers in Cardiovascular Medicine, 2022)
Background Animal studies have shown that midazolam can increase vulnerability to cardiac ischemia, potentially via circadian-mediated mechanisms. We hypothesized that perioperative midazolam administration is associated with an increased incidence of myocardial injury in patients undergoing non-cardiac surgery (MINS) and that circadian biology may underlie this relationship. Methods We analyzed intraoperative data from the Multicenter Perioperative Outcomes Group for the occurrence of MINS across 50 institutions from 2014 to 2019. The primary outcome was the occurrence of MINS. MINS was defined as having at least one troponin-I lab value ≥0.03 ng/ml from anesthesia start to 72 h after anesthesia end. To account for bias, propensity scores and inverse probability of treatment weighting were applied. Results A total of 1,773,118 cases were available for analysis. Of these subjects, 951,345 (53.7%) received midazolam perioperatively, and 16,404 (0.93%) met criteria for perioperative MINS. There was no association between perioperative midazolam administration and risk of MINS in the study population as a whole (odds ratio (OR) 0.98, confidence interval (CI) [0.94, 1.01]). However, we found a strong association between midazolam administration and risk of MINS when surgery occurred overnight (OR 3.52, CI [3.10, 4.00]) or when surgery occurred in ASA 1 or 2 patients (OR 1.25, CI [1.13, 1.39]). Conclusion Perioperative midazolam administration may not pose a significant risk for MINS occurrence. However, midazolam administration at night and in healthier patients could increase MINS, which warrants further clinical investigation with an emphasis on circadian biology.